Move over and make space for lived experience criminology: Why we do “lived experience” - Antojado, Dwayne (Journal of criminology, 2025)
This paper points out the disparity in the recognition of lived experiences between the United States – where convict criminology is more established, and Australia. The authors call for a shift from convict to lived experience criminology in Australia, emphasising the need for diverse methodologies beyond autoethnography. It is pertinent to note here that the authors of this paper, Antojado and McPhee, are formerly incarcerated scholars, serving time in various prisons in Australia. We use our expertise by experience to inform our work. This paper discusses the challenges individuals with Lived Prison and/or Criminal Legal Sanction Experience (LPCLSE) face in gaining academic recognition and critiques the academic community's hesitance to accept us as equals. It stresses the significance of lived experiences in deepening the understanding of the social and emotional aspects of crime and justice. Integrating these narratives into criminology is argued to challenge and enrich present epistemological frameworks, leading to more holistic and empathetic research and policy-making in the criminal legal sector. The authors advocate for redefining criminological expertise to value experience equally with academic qualifications and call for academic support for the development of lived experience criminology. This is seen as crucial for a more inclusive and comprehensive understanding of crime and justice discourses, urging criminologists to embrace and develop this subfield. Using the work of bell hooks and Dean Spade, we also turn our attention to the reasons for why people with lived experience expertise might engage in this type of work, arguing that it is a way for us to make/unmake meaning, to live with purpose, to live with guilt, and to love.